2017
DOI: 10.1183/13993003.00746-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atopobium and Fusobacterium as novel candidates for sarcoidosis-associated microbiota

Abstract: Sarcoidosis is a granulomatous disease that mainly affects the lung. A role of microbial factors in disease pathogenesis is assumed, but has not been investigated systematically in a large cohort.This cross-sectional study compared the lung microbiota of 71 patients with sarcoidosis, 15 patients with idiopathic pulmonary fibrosis (non-infectious controls) and 10 healthy controls (HCs). Next-generation sequencing of 16S DNA was used on bronchoalveolar lavage samples to characterise the microbial composition, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 48 publications
2
53
0
1
Order By: Relevance
“…We next identi ed Atopobium, Selenomonas and Faecalibacterium may predict the different malnutrition status in CRC patients using ROC analysis. It brought to our attention that Atopobium and Fusobacterium were identi ed as sarcoidosis-associated bacteria, which may enable new insights into the pathogenesis and treatment of CRC [12]. In CRC, the abundance of Atopobium parvulum and Actinomyces odontolyticus, were signi cantly increased only in multiple polypoid adenomas and/or intramucosal carcinomas, indicating those two bacteria may be considered as the microbiome therapy target in CRC [13].…”
Section: Discussionmentioning
confidence: 99%
“…We next identi ed Atopobium, Selenomonas and Faecalibacterium may predict the different malnutrition status in CRC patients using ROC analysis. It brought to our attention that Atopobium and Fusobacterium were identi ed as sarcoidosis-associated bacteria, which may enable new insights into the pathogenesis and treatment of CRC [12]. In CRC, the abundance of Atopobium parvulum and Actinomyces odontolyticus, were signi cantly increased only in multiple polypoid adenomas and/or intramucosal carcinomas, indicating those two bacteria may be considered as the microbiome therapy target in CRC [13].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, infectious agents gained the most research attention throughout the years largely due to the clinical and histological similarities between sarcoidosis and tuberculosis. Except mycobacteria [4,5], the role of other bacteria such as propionibacteria [6][7][8][9], as well as viruses [10], fungi [11,12] and the lung microbiome overall [13,14] has been investigated in numerous molecular studies. The causal role of these infectious agents is still obscure as results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the European Respiratory Journal, ZIMMERMANN et al [6] present the largest study so far and describe the microbial composition in 71 patients with sarcoidosis, 10 healthy controls and 15 IPF patients. Mycobacterial DNA was only present in two sarcoidosis patients.…”
mentioning
confidence: 99%
“…Because the sample size in the ZIMMERMANN et al [6] study was large, the authors stratified the patients by lung phenotype according to radiographic Scadding stages. In comparison with controls, ZIMMERMANN et al [6] found that the increase in Atopobium sp. was associated with stage I (n=17) and II (n=39) and the increase in Fusobacterium sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation